STANDARDISING THE QUALITY AND PRICE OF RICE IN LANGSA ACEH: A STUDY OF LEGAL COMPARATIVE - Nuri Nizla Istianah; Muhammad Amin (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2024)
The instability of rice prices can affect the purchasing power of the community and disrupt social and economic balance. This study aims to examine rice pricing in Kota Langsa, focusing on quality standardization, the application of the Mabi’ concept in Islamic jurisprudence (fiqih muamalah), and its relevance to Peraturan Badan Pangan Nasional No. 2 Tahun 2023 (National Food Agency Regulation No. 2 of 2023). The research employs a socio-legal approach with descriptive analysis, utilizing primary data from interviews and secondary data from related documentation. The findings reveal that rice quality is the main factor in price determination, aligning with the Mabi’ concept, which emphasizes clarity of goods to ensure fair and transparent transactions. Quality standardization based on government regulations ensures that products meet predetermined quality criteria. Additionally, factors such as production costs, distribution, and fluctuations in rice paddy prices also influence price dynamics. This study concludes that the integration of the Mabi’ principle, government regulations, and a healthy market mechanism can create fair rice price stability, benefiting both consumers and producers while supporting the sustainability of the national food system.